Complete genome sequence and phylogenetic analysis of medicinal plant Abrus cantoniensis for evolutionary research and germplasm utilization. Issue 3 (24th June 2022) - Xu, Shiqiang; Li, Fangping; Wu, Bingqi; Mei, Yu; Wang, Jingming; Wang, Jihua
Abstract: Abrus cantoniensis Hance, a native medicinal plant in southern China, is officially recorded in the Chinese Pharmacopoeia. Here, we presented the first high‐quality genome in Abrus genus, A. cantoniensis genome, as well as the detailed genomic information. The assembled genome size was 381.27 Mb with a scaffold N50 of 18.95 Mb, and 98.97% of the assembled sequences were anchored on 11 pseudochromosomes. The A. cantoniensis genome comprised 25, 058 protein‐coding genes and 45.12% of the assemblies were repetitive sequences. Comparative genome analysis suggested that chromosome translocation and inversion played an important role in the differentiation of Abrus . In addition, 24 toxin‐related genes were identified, which formed two tandem gene clusters on chromosomes 2 and 3. The chromosome‐level genome of A. cantoniensis obtained in this work provides a valuable resource for understanding the evolution, active ingredient biosynthesis, and genetic improvement for A. cantoniensis and Abrus species. Core Ideas: We presented the first high‐quality complete genome in Abrus genus, A. cantoniensis genome. We dissected the toxin‐related genes and detected two tandem gene clusters similar with plant BGCs. The research revealed translocation and inversion of chromosomes played an important role in the differentiation of Abrus .